Informasi Laporan Keuangan, Kondisi dan Prestasi Perusahaan - Elfreda Aplonia Lau (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
A proof that the company manage its finances effectively is to detect the source and use of funds. Plans for the utilization of f